Punching Shear Failure Regulation of Reinforced Concrete Beams Subjected to Close-in Explosion. Issue 1 (January 2022) - Tang, Hong; Zhai, Hongbo; Su, Jianjun; Fu, Teng
Abstract: Aiming at the damage effect of reinforced concrete beams subjected to close-in explosion, numerical simulation and dimensional analysis are carried out to study the damage of beams under close-in explosion with spherical charge. The damage characteristics of beams were obtained by the methods of AUTODYN and DYNA. Using dimensional analysis, the relationship between the damage characteristics of reinforced concrete beams and the stand-off distance is deduced. The empirical equation of the beam punching shear failure characteristics is fitted on the basis of numerical simulation. The results show that the simulation method is more efficient than the fluid-solid coupling calculation; the proposed empirical equation is in good agreement with the experimental results. The relationship between failure width and the stand-off distance obtained by the fitting and the modelling method have reference value for the research on the damage effect of reinforced concrete beams.